Pengaruh Likuiditas, Profitabilitas dan Kebijakan Dividen Terhadap Nilai Perusahaan Dengan Ukuran Perusahaan Sebagai Variabel Moderasi - Khoirunisa', Fatmadali; Mahirun; Meliza (Program Studi Manajemen Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2024)
This study aims to test and analyze the influence of liquidity, profitability and dividend policy on company value with company size as a moderation variable. The population in this study is LQ45 Low Carbon Leader listed on the Indonesia Stock Exchange for the 2021-2023 period. Sample withdrawal using purposive sampling, the sample in this study amounted to 65 data. The analysis technique uses the WarpPls program version 8.0. The results in this study show that the current ratio (CR) has a significant negative effect on price book value (PBV), return on asset (ROA) has a significant positive effect on price book value (PBV), dividend payout ratio (DPR) has a significant positive effect on price book value (PBV), company size does not moderate current ratio (CR) to price book value (PBV), company size strengthens return on assets (ROA) to price book value (PBV) and company size strengthens dividend payout ratio (DPR) to price book value (PBV).